1997
DOI: 10.1182/blood.v90.6.2213
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X-Inactivation in Carriers of X-Linked Dyskeratosis Congenita

Abstract: A gene causing Dyskeratosis Congenita (DC), a rare genetic disorder associated with bone marrow failure, has been mapped to chromosome Xq28, but autosomal inheritance of the disease has also been reported. We have investigated the pattern of X-inactivation in the peripheral blood of carriers of DC using the methylation-sensitive Hpa II site in the androgen receptor gene (HUMARA). In 5 different families in which the inheritance of DC appears to be X-linked, all 16 carriers showed skewed X-inactivation patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 16 publications
4
19
0
1
Order By: Relevance
“…Finally, because female carriers of DKC1 mutations frequently develop biased X‐inactivation due to the growth advantage of WT DKC1 ‐expressing cells , we performed the X chromosome inactivation analysis with the HUMARA assay to look for evidence of skewed X‐inactivation in peripheral blood of the patient's mother. Taking advantage of the microsatellite allele of the human androgen receptor shared between the patient and his mother as a marker of co‐segregating mutant DKC1 , we found that the mother's X‐inactivation was strongly biased towards expression of the WT DKC1 allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, because female carriers of DKC1 mutations frequently develop biased X‐inactivation due to the growth advantage of WT DKC1 ‐expressing cells , we performed the X chromosome inactivation analysis with the HUMARA assay to look for evidence of skewed X‐inactivation in peripheral blood of the patient's mother. Taking advantage of the microsatellite allele of the human androgen receptor shared between the patient and his mother as a marker of co‐segregating mutant DKC1 , we found that the mother's X‐inactivation was strongly biased towards expression of the WT DKC1 allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proband was heterozygous for the DKC1 G486R polymorphism (rs150319104; minor allele frequency in 1,000 genomes ¼ 0.001). Normally females heterozygous for pathogenic DKC1 mutations have no phenotype or are only very mildly affected, but all female carriers of disease causing DKC1 mutations show extreme skewing of X-inactivation owing to a competitive advantage of cells expressing the wild-type allele following random X-inactivation [7]. We reasoned that a sensitive test for the status of the DKC1 G486R mutation would be to test the mother, who is heterozygous for the mutation, for skewed X-inactivation.…”
Section: Case Reportmentioning
confidence: 99%
“…The situation is different when there is a selective disadvantage for the cell that carries the mutant allele on the active X chromosome. This is the case for carriers of several severe X‐linked disorders, such as Wiskott–Aldrich syndrome 42, α‐thalassaemia/mental retardation syndrome 43, dyskeratosis congenita 4445 and Barth syndrome 46. In these disorders, post‐inactivation selection probably takes place, leading to a completely skewed X‐inactivation pattern and a normal phenotype.…”
Section: Inactivation In Different Tissuesmentioning
confidence: 99%